83 Clinical and haemodynamic status beyond 3 months of mechanical support with the heartware ventricular assist device. (9th June 2011) - Gordon, B; McDiarmid, A; Robinson, N; Wrightson, N; Parry, G; Schueler, S; MacGowan, G
Abstract : Introduction: Limited data exist on the longer term clinical and haemodynamic impact of the HeartWare left ventricular assist device (HVAD®) when used as a bridge to heart transplantation. Patients who had a device longer than 3 months were reviewed. Methods: 26 patients had a HVAD implanted from 07/2009 to 07/2010 (mean age 46.8 years, 18 male, 5174 total days of support). Baseline and follow-up NYHA functional class, peak VO2 (bicycle exercise), right heart haemodynamics, biochemistry and mortality outcome were compared using paired t test. Results: 22/26 (85%) patients survived beyond 3 months. 4 patients died before (mean survival 40 days, 2 stroke and 2 multi-organ failure) and 2 died after (mean survival 173 days, 1 stroke, 1 right heart failure) discharge from hospital. 2 patients were transplanted (at 3 and 241 days after implant) and 1 had recovery of LV function. Follow-up data is available for 14/20 survivors (mean 197 days from implant). Significant results are shown in the Abstract 83 table 1 . There was no significant change in peak VO2 (9.9±1.8 to 12.9±3.8, p=0.08), haemoglobin (12.7±1.7 to 12.1±1.2, p=0.3) or creatinine (122±41 to 105±38, p=0.19). Conclusions: The HVAD® results in significant improvement in functional class, right heart haemodynamics, cardiac output and sodium levels beyond 3 months of therapy. Ongoing randomised clinical trials will establish the long-term outcome of this device.